2019
DOI: 10.32725/jab.2019.011
|View full text |Cite
|
Sign up to set email alerts
|

Positive association between a polymorphic locus near the LBX1 gene and predisposition of idiopathic scoliosis in Southeastern European population

Abstract: Idiopathic scoliosis (IS) is a common medical condition in children, characterized by three-dimensional spinal curve and strong evidence of genetic predisposition. The purpose of the present case-control study is to examine the association between the polymorphic variant rs11190870 (T/C), near the LBX1 gene, and IS predisposition in distinct subgroups based on age at onset, family history and gender. A total of 127 IS patients and 254 unrelated controls of Southeastern European descent were recruited. The geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Further, the forward citation search located 11 more relevant reports. Therefore, 19 studies in total were included in this review 14–32 . The flow diagram of the study selection is illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the forward citation search located 11 more relevant reports. Therefore, 19 studies in total were included in this review 14–32 . The flow diagram of the study selection is illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, 19 studies in total were included in this review. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] The flow diagram of the study selection is illustrated in (n = 3), respectively. Apart from the human subjects, mice and zebrafish were employed as study subjects.…”
Section: Selection Of Sources Of Evidencementioning
confidence: 99%
“…Fan et al [58] found an OR = 1.85 for the SNP rs11190870, which was higher than those reported in this systematic review. Similarly, Jiang et al [59], Liu et al [28], and Nikolova et al [60] analyzed the same SNP providing an OR = 1.51, OR = 0.61, and RR = 1.37, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…The obtained results by descriptive analysis (frequency, mean, minimum, maximum, and standard deviation values) were summarized in tables. The hypothesis testing with a level of significance <0.05 was processed by the twotailed Fisher's Exact Test with the statistical package IBM SPSS Statistics 19.0 for Windows [13], [14].…”
Section: Statistical Data Processingmentioning
confidence: 99%